Growth, carcass and digestive system changes in hybrid village chickens after uropygialectomy - Jawad, Hasan Saad Abdulhussein (2016)
Akar Putra is a hybrid village chicken; the cross breeding process was happened by chance when the wild jungle fowl interred Universiti Putra Malaysia (UPM) ground and mated with their Ayam Kampung (Native chicken). Nonetheless, there is a dearth of information relating to the Akar Putra chicken strain, particularly the morphology of its digestive system. Uropygial Gland (UG) is the most prominent integument gland in the birds. It is puzzling that little is known about its morphology and function. The suggested functions of this gland can be placed into four groups: 1) feather maintenance; 2) water-proofing; 3) intraspecific communication and 4) defense against predators. This thesis introduces a new technique to improve the production performance of the chicken through ablation of the uropygial gland which called Uropygialectomy (UP). This application will cause an upset in the poultry industry as well as will significantly contribute towards its development by increasing the economic viability obtained through an increase the chicken product. Previous method of Uropygialectomy included removing the uropygial gland completely and that usually attached by severe bleeding with hard stress exposure of the chicken. While, our modification method includes removing parts from the gland (half lobes, half isthmus and papillae). That modification was taken place in order to make UP operation safer, practical, applicable and shows a significant improvement of production performance. Therefore, this study was carried out to address the production performance, carcass characteristics, external morphological changes, anatomical changes of digestive system, growth hormone concentration and histology of digestive system investigation of 120 Akar Putra chickens strain following the ablation of the uropygial gland. The experiment comprised five treatments, with 3 replicates for each. The treatments consisted of a control T1; Uropygialectomy was applied with T2, T3, T4 and T5 treatments at 3, 4, 5 and 6 weeks of age respectively. The results revealed remarkable significant (P < 0.05) enhancing for UP treatments than a control group in all of males and females' body weight, weight gain, feed intake and feed conversion ratio measurements. Furthermore, the results indicated that UP treatments caused significantly improvement (P < 0.05) concerning body weight, carcass weights and dressing percentage with or without eating giblets. Additionally, significant different at level (P < 0.05) was observed in the traits of males' breast and back relative weight. Additionally, there was a significant effect at level (P < 0.05) in the females' breast relative weight trait; however, T2 surpasses other treatment groups T1, T3, T4 and T5 with relation to the most carcass traits involved in this experiment. The external morphological comparison results between UP treatments and control at week 12 shows that the males of UP treatments had higher values in bird length, growth rate, breast diameters and lengths of neck, back, keel bone and extremities than males of the control group. Likewise, females of PU treatments surpassed females of the control group in bird length, growth rate, neck length, breast width and comb length. The anatomical evaluations revealed that the males of UP treatments had more length (P < 0.05) esophagus 9.9-16.2%, proventriculus 11.1-34.4%, gizzard 26.7-220%, pancreas 0-20.4%, jejunum 4.9-26.1 and colon 18.1-60.6 than their control group counterparts. Furthermore, females of UP treatments had (P < 0.05) longer esophagus 6.8-22.3%, pancreas 8.3-33.3% and cecum 13-26% compared with females in control. Histologically, surgical removing of the uropygial gland, especially at week 3 had greater (P < 0.05) effect on the total duodenum, jejunum and ilium wall thickness. In addition, effects (P < 0.05) were observed on the wall thickness of males’ cecum and colon. Moreover, the wall layers of: esophagus, proventriculus, gizzard and rectum were not affected by the treatment. However, removing the uropygial gland showed significant impact (P < 0.05) in males’ growth hormone concentration level at week 7 and (P < 0.05) effect at week 12 in both sexes. In conclusion, the results of current study demonstrated that partial ablation of the uropygial gland, especially at week 3 of age had a positive effect on the production performance, carcass characteristics, external morphological measurements, anatomy and histology of digestive system organs as well as the growth hormone concentration of the Akar Putra chicken strain. These enhancement in the body performance can be justified that UP will contribute in retention the essential fatty acids in the body and avoid its attraction inside the UG, then secreted out of the body. In another hand, it will support the work of prostaglandins, which drives from Arachidonic fatty acid, resulting in the production of growth hormone. The improvement in the productive performance, carcass characteristics, phenotypic traits, as well as the anatomy and histology of the digestive system were as a consequence to increase of growth hormone secretion by the anterior pituitary gland. Moreover, the improvement in the body morphology was as a consequence to increase of the steroid hormones' levels by stopping the function of the uropygial gland in converting progesterone to testosterone.